Modeling of Surface Tension and Adhesive Force on Two Fluid to Porous Medium Interaction by SPH Method - Setiadi, Herlan
Surface tension and adhesive force play an important role on the uid and the medi- ums around it. In this theses, the surface tension and adhesion force is modeled by Smoothed Particle Hydrodynamics. The uid domain is discretized by the method into a set of Lagrangian particles. The interaction is easier to model rather than other method due to the particles carry the physical informations. The surface boun- dary of the uid is tracked implicitly by smoothed color eld scheme. The dierence of the normal vector of the smoothed color eld is used to determine the surface boundary of the uid. The magnitude of the cohesive and adhesive force is com- puted by the smoothing function of the SPH method. The magnitude of the force increases ad the the distance of the particle and its neighbor decreases. The method is applied to simulate water and oil exceed the porous medium due to gravitation. The study is aimed to test the developed surface tension and adhesion model to the experiment and investigate the sensitivity of the method to the parameters. The results which are obtained from the simulations show the method is very sensitive to the parameters and the interaction to the wall.